Genomic, proteomic, and immunologic associations with a durable complete remission of measurable metastatic melanoma induced by a patient-specific dendritic cell vaccine - Robert O. Dillman; Gabriel I. Nistor; Aleksandra J. Poole (Taylor & Francis Group, 2020)
This report describes efforts to understand the immune mechanism of action that led to a complete response in a patient with progressive, refractory, metastatic melanoma after treatment with a therapeutic vaccine consisting of autologous dendritic cells (DC) loaded with autologous tumor antigens (ATA) derived from cells that were self-renewing in cell culture. Her histocompatibility type proved to be HLA B27 with extensive mutations in the HLA-A locus. Exomic analysis of proliferating tumor cells revealed more than 2800 non-synonymous mutations compared to her leukocytes. Histology of resected tumor lesions showed no evidence of an existing or suppressed immune response. In in vitro mixed cell cultures, DC loaded with ATA induced increased IL-22 expression, and a four-fold increase in CD8 + T lymphocytes. Cryopreserved blood samples obtained at week-0, 1 week before the first of three-weekly vaccine injections, and at week-4, 1 week after the third dose, were analyzed by protein array and compared for 110 different serum markers. At baseline, she had marked elevations of amyloid A, IL-12p40, IL21, IL-22, IL-10, IL-16, GROa, TNF-alpha, IL-3, and IL-2, and a lesser elevation of IL-15. One week after 3 weekly vaccinations she had a further 80% increase in amyloid A, a further 66% increase in IL-22, a 92% decrease in IL12p40, a 45% decrease in TGF-β and 26% decrease in IL-10. The data suggested that by 3 weeks after the first DCV injection, vaccine-induced changes in this particular patient were most consistent with enhanced innate and Th1 immune responses rather than Th2 or Th17.